2012
DOI: 10.4103/0019-5049.93344
|View full text |Cite
|
Sign up to set email alerts
|

Oral pregabalin premedication for attenuation of haemodynamic pressor response of airway instrumentation during general anaesthesia: A dose response study

Abstract: Background:The airway instrumentation of direct laryngoscopy and tracheal intubation are powerful noxious stimuli that should be attenuated by appropriate premedication, smooth induction and rapid intubation. The present study evaluated the safe and clinically effective dose of oral pregabalin premedication for attenuation of haemodynamic pressor response of airway instrumentation.Methods:A total of 90 normotensive adult consented patients aged 24–56 years, ASA grade I and II, of both gender were randomized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 19 publications
4
19
0
3
Order By: Relevance
“…The results of the current study are in agreement with those of studies performed by Singh and Arora [17], Montazeri et al [18] and Rastogi et al [16], who demonstrated that the hemodynamic pressor response to airway instrumentation was attenuated by the use of oral pregabalin as a premedication. Similar results have also been reported by Salman et al [7] and Eren et al [19] who observed the a significant increase in HR and BP in the control group and atte- [12].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results of the current study are in agreement with those of studies performed by Singh and Arora [17], Montazeri et al [18] and Rastogi et al [16], who demonstrated that the hemodynamic pressor response to airway instrumentation was attenuated by the use of oral pregabalin as a premedication. Similar results have also been reported by Salman et al [7] and Eren et al [19] who observed the a significant increase in HR and BP in the control group and atte- [12].…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, Rastogi et al studied the effect of different doses of pregabalin premedication for attenuating the hemodynamic pressor response to airway instrumentation during general anesthesia [16]. They reported that the HR increased significantly immediately after laryngoscopy and intubation in all groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregabalin, a gabapentinoid compound, is an antiepileptic drug that is effective for treating several kinds of pain, including neuropathic, incisional, and inflammatory pain [6], as well as anxiety [7] and provides hemodynamic stability [8]. Pregabalin also attenuates OIH in human and animal studies [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There are various studies regarding the use of pregabalin for attenuation of pressor response during laryngoscopy and intubation in normotensive patients. 7,8 However only a few trials have evaluated hemodynamic pressor response among controlled hypertensive patients. The inhibitory effects of pregabalin on membrane voltage-gated calcium channels can be the reason for its response to laryngoscopy and intubation.…”
mentioning
confidence: 99%